CRISPR/Cas-Based Ex Vivo Gene Therapy and Lysosomal Storage Disorders: A Perspective Beyond Cas9 - Andrés Felipe Leal; Luis Eduardo Prieto; Harry Pachajoa (Cells)
Lysosomal storage disorders (LSDs) are inherited metabolic conditions characterized by lysosomal enzyme deficiencies leading to substrate accumulation. As genetic diseases, LSDs can be treated with gene therapies (GT), including the CRISPR/Cas systems. The CRISPR/Cas systems enable precise and programmable genome editing, leading to targeted modifications at specific genomic loci. While the classical CRISPR/Cas9 system has been extensively used to generate LSD disease models and correct disease-associated genetic alterations through homologous recombination (HR), recently described Cas proteins as well as CRISPR/Cas9-derived strategies such as base editing, prime editing, and homology-independent targeted integration (HITI) offer a novel way to develop innovative treatments for LSDs. The direct administration of the CRISPR/Cas9 system remains the primary strategy evaluated in several LSDs; nevertheless, the ex vivo CRISPR/Cas9-based approach has been recently explored, primarily in central nervous system-affecting LSDs. Ex vivo approaches involve genetically modifying, in theory, any patient cells in the laboratory and reintroducing them into the patient to provide a therapeutic effect. This manuscript reviews the molecular aspects of the CRISPR/Cas technology and its implementation in ex vivo strategies for LSDs while discussing novel approaches beyond the classical CRISPR/Cas9 system.